Factors Influencing the Incidence of Measles in Under Fives in Tamale Municipality - Kasu, E.S. (University of Ghana, 2001)
Tamale Municipality is the smallest of the 13 districts in the Northern Region. It serves as the capital of both the Region and the district. The incidence of measles in Tamale is among the highest in the region. Most of the cases were in children under five. Despite efforts to control the disease, the incidence has remained almost the same. A case control study and seroprevalence study were jointly carried out as a single study to determine the factors that influence the incidence of measles in under five children. In the case control study, 75 children between 0-60 months who had measles in 2000 were randomly selected as cases and traced to their communities and were paired with controls, who were children who did not have any history of measles in the same communities as cases. In addition, a seroprevalence study of measles antibodies was undertaken in a convenience sample of 100 preschool children between 2-5years to determine the efficacy of the measles vaccine. The mothers of cases and the controls were interviewed to determine their children's immunization status, socioeconomic characteristics, beliefs and practices with respect to measles. The study found out that sixty-eight percent of the cases that had measles was vaccinated against measles. Twelve percent of the cases developed measles before they were 9 months old. All the cases recovered from measles. The immunization status of those who had measles and those who did not were different (p<0.05). Significant number of controls completed their immunization against childhood diseases before one year of age than cases (p<0.05). Completion of immunization schedules by one year of age was important in reducing measles incidence among the children studied. Adverse effects of immunizations did not deter mothers from immunizing their children and was not important in influencing the incidence of measles in the study The background characteristics of the mothers/caregivers of the cases and controls were similar in terms of education, marital status, religion, occupation and income level. Most of the respondents of cases and controls were poor in that they earned less than 0100,000 per month and live in poor houses. These factors are not significant in determining the incidence of measles in the Tamale Municipality. In the seroprevalence study of 67% of the preschool children examined, had protective antibody levels for measles. The seroconversion rate in the vaccinated day nursery children was 72.6%. This is lower than 95% that was expected.
Thesis(MPH)- University of Ghana